Sex- and estrous-specific effects of paradoxical sleep deprivation: neurobehavioral changes and hippocampal neuroinflammation - Olsen, Laura K.; Jones, Krysten A.; Moore, Raquel J.; McCubbins, Hunter; Curtner, Frances S.; Sharma, Birendra; Hatcher-Solis, Candice N. (Frontiers in Sleep, 2025)
With millions suffering from sleep disorders in today's society, a better understanding of sleep disruption related to cognitive outcomes is urgently needed. To that end, a preclinical investigation into the effects of paradoxical sleep deprivation (PSD) on neurobehavioral outcomes and associated hippocampal neuroinflammation was conducted in male and female rats. Due to epidemiological identification of sex differences in many aspects of sleep disorders, sex and estrous-cycle stage factors were investigated. Sprague-Dawley rats underwent 120 h of PSD using a modified multiple-platform “flowerpot” method. At 96 h of PSD, animals were trained on neurobehavioral Novel Object Recognition (NOR) and Passive Avoidance Task (PAT) paradigms. Before NOR/PAT testing, at 120 h PSD, the Elevated Zero Maze (EZM) was used to assess anxiolytic-like behavior. PSD-impaired PAT performance among males and females. In males after PSD, anxiolytic-like and locomotor behavior was increased, and NOR performance was impaired. Based on estrous cycle stages determined by cytological analysis of daily wet smears, females were found to exhibit estrous-specific differences across all neurobehavioral paradigms, with increased anxiolytic-like behavior and impaired PAT performance only among PSD females in estrus. Immunohistochemical analysis of the hippocampus after 120 h of PSD found microgliosis, but not astrogliosis, in the CA1/2 of males and females in estrus. This study contributes to a better understanding of the sex- and estrous-specific differences in sleep disruption–induced neurobehavioral outcomes and associated hippocampal inflammation. Further research is needed to investigate the molecular mechanisms underlying the interaction between estrous cycle, hippocampal microgliosis, and sleep-disrupted cognitive outcomes.